Decomposing Euro Area Sovereign Debt Yields into Inflation Expectations and Expected Real Interest Rates - MIRDALA, Rajmund (Journal of Advanced Research in Law and Economics; Vol 6 No 4 (2015): JARLE Volume VI, Issue 4(14), Winter 2015, 2017)
Quantitative easing conducted by European central bank to fight persisting risks of deflation is drawing an attention of increasing number of empirical studies. Moreover, effectiveness of monetary policy at near zero inflation rates reveals lot of issues on whether interest rates really have a lower bound around zero percent. As a result, traditional views on the role of inflation expectations and expected real interest rates in the long-term interest rates determination face the challenge of fundamental revision. In the paper we analyze relative contributions of inflation expectations and expected real interest rates to long-term interest rates on government bonds leading path as well as their responses to both types of shocks in the Euro Area member countries using SVAR methodology. We also decompose long-term interest rates into transitory and permanent components. Our research revealed considerable differences in the role of inflation expectations and expected real interest rates shocks in determining long-term interest rates between core and periphery countries of the Euro Area. The crisis period even intensified this trend.